Do cross-border bank mergers and acquisitions lead to greater efficiency? Evidence from Indonesia - Rudi Kurniawan; Dominicus Savio Priyarsono; Widodo Ramadyanto; Tania Chusna Azzahra (Jurnal Fokus Manajemen Bisnis, 2026)
This study investigates whether cross-border mergers and acquisitions enhance the efficiency of Indonesian private commercial banks, an issue that remains inconclusive in the emerging-market literature. The purpose of this research is to assess the impact of foreign ownership on efficiency and identify its key determinants, specifically by testing the validity of efficiency and synergy theories in an emerging market context. Quarterly financial data from 2017 to 2024 for 10 banks, 5 foreign-acquired and 5 non-acquired, are analyzed. Bank efficiency is measured using data envelopment analysis, which assesses technical, pure technical, and scale efficiency. To estimate causal effects, propensity score matching combined with a difference-in-differences approach is used, while Tobit regression is used to examine determinants of efficiency. The results show that cross-border mergers and acquisitions do not lead to statistically significant overall efficiency gains, despite heterogeneous effects across individual banks. Furthermore, bank size has a significant negative effect on efficiency, while profitability and capital adequacy exhibit mixed effects. These findings suggest that foreign acquisitions do not automatically improve bank efficiency, highlighting post-merger integration challenges. Theoretically, this study contributes by challenging the synergy theory, demonstrating that ownership transformation does not automatically yield operational synergies, and enriching the banking efficiency literature with a robust, high-frequency framework. In practice, these insights serve as a crucial strategic guideline for bank management to prioritize post-merger cultural and operational integration over simple scale expansion, while also assisting financial regulators in formulating more prudent cross-border banking acquisition policies.